Sex Education in Family: Study on Children Living Far Apart with The Family - Pradikto, Bayu; Sofino, Sofino (Universitas Negeri Semarang, 2019)
Premarital sex is still a concern for parents and it is not acceptable behaviour in the community. Besides, it can cause infectious diseases, death of young mothers, susceptible to abortion, and other health risks. The purpose of the study was to obtain an overview of the family sex education of children living far away from home. The study used a qualitative approach with descriptive methods with data collection techniques using open-ended polls and in-depth interviews. A total of 43 students ‘ population of non-formal education study semester II who lives in boarding or contact in the city of Bengkulu (far from parents). Results show that students seldom discuss love, sex, parenting and family planning in a family environment. Topics discussed in the home environment of sex education are only limited to planning education is not the plan of the family. Majority of parents using the story approach to introducing sex education with limited. The way parents monitor the sexual behaviour of children far apart by calling the child, asking the close relatives, friends and owners of the Boarding house and strengthening the religious enhancement. Next way special girls are visited at least once a month.